Changes in the Meibomian Gland After Exposure to Intense Pulsed Light in Meibomian Gland Dysfunction (MGD) Patients. (4th March 2018) - Yin, Yue; Liu, Ninghua; Gong, Lan; Song, Nan
ABSTRACT: Purpose : To observe (1) changes in meibomian gland (MG) after exposure to intense pulsed light (IPL) and (2) to understand the mechanism by which IPL treats meibomian gland dysfunction (MGD) in patients. Methods : A cohort study, including 35 MGD patients, was conducted. IPL treatment was administered in one group (IPL group; n = 18), and eyelid hygiene in another (control group; n = 17) for 3 months. All patients were given artificial tears during the treatment period. Associated ocular-surface indexes (ocular surface disease index, OSDI; tear breakup time, TBUT, Schirmer 1Test, corneal staining, and conjunctival staining), MG function, MG macro-morphology, and MG micro-morphology were examined before and after treatment. The relationships between the change in symptom score and the change in the other indexes (related ocular-surface indexes, MG functional indexes, and MG morphological indexes) were evaluated. Results : There was no statistical difference in pretreatment between the IPL and the control groups in terms of age, gender, related medical history, MGD stage, and all examined indexes, with the exception of conjunctival staining. OSDI, TBUT, meibum quality, MG expressibility, and MG dropout improved after treatment in both of the two groups (all P < 0.05). The MG microstructure indexes, including the MG acinar longest diameter (ALD), MG acinar unit density (AUD), and the positive rate of inflammatory cells (ICs) around glandular structures were significantly improved in the IPL group. No improvements of microstructure were found in the control group. Conclusion : IPL treatment improves the symptom score of patients, associated ocular-surface indexes, MG function, and MG macrostructure as well as eyelid hygiene. And IPL treatment particularly improves MG microstructure and decreases MG inflammation in MGD patients.